Effects of arbuscular mycorrhizal fungi associated with phenolic compounds on the growth of papaya - Martins, Marco Antonio; Gonçalves, Geisa Fonseca de; Soares, Ana Cristina Fermino (Pesquisa Agropecuaria Brasileira, 2000)
This work was carried out under greenhouse conditions to evaluate the effects of different species of arbuscular mycorrhizal fungi (AMF), associated with phenolic compounds (rutin and quercetin) on the growth and P contents of papaya plants under two doses of P (0 and 50 mg kg-1). The fungi used were Glomus clarum (Gc), G. macrocarpum (Gm) and a population of native fungi (Nf), which was isolated from a papaya plantation in the Experimental Station of PESAGRO-RIO, Macaé, RJ, Brazil. At the dose 0 mg kg-1 of P, the inoculation with Gc led to significant increases in dry matter and P contents of plant shoots, independently of the addition of the compounds rutin or quercetin. However, in the case of Gm, significant increases was only observed in treatments in which rutin was added, indicating that this compound was able to increase the effectiveness of this fungal species. There was no significant effects of Nf on the dry matter and P content of plant shoots. Increasing the doses of P (50 mg kg-1), both AMF species used did not lead to any significant increase in dry matter and P content of papaya plant shoots.